Zwischenruf - Craus, Sandy (Germany, 2010)
The film is based on the idea that the perception of cultural differences is determined by individual backgrounds. "Call" disturbs this setting by using a text from the Old Testament, Isaiah 11: 6-9 which implies that all religions can or will co-exist peacefully.
Verzio Film Festival Submission
Keywords: Documentary films